Analisis Pengaruh Inklusi Keuangan Syariah, Perbankan Syariah, dan Pasar Modal Syariah terhadap Pertumbuhan Ekonomi di Indonesia Periode 2013-2023 - Vika Anjani; Cupian Cupian (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to evaluate the long-run and short-run relationship between the Islamic capital market and Islamic banking on Indonesia's economic growth over the period 2013-2023. Using a quantitative approach and the Vector Error Correction Model (VECM) method, this study analyzes the dynamics between these variables. The data used includes the Indonesian Sharia Stock Index (ISSI), Islamic bonds, Islamic banking third-party funds (DPK), non-performing financing (NPF), and real gross domestic product (GDP) as an indicator of economic growth. The analysis shows that in the long run, both the Islamic capital market and Islamic banking contribute significantly to economic growth. However, in the short term, only a few variables show a significant effect. These findings confirm the strategic role of the Islamic financial sector in supporting sustainable economic growth, as well as the importance of strengthening and developing Islamic instruments to support national economic stability and progress.